“The Curious Case of Benjamin Button” – Time and Space in Political Analysis - Vasileva, Evgeniya (Research Papers, 2019)
The political analysis does not describe; it transforms and rearranges the meaning of the world. The political analysis is a practice of thinking, concerned about the current state and prosperity of communities and their relations. Within the framework of this understanding, the article analyses time and space as political categories since every political system can be completely defined through them. Time and space are variables and can be in a condition of crisis, urgency, importance or necessity. They could be disarranged, and could affect positively or negatively the collective existence and action in the political communities.To interpret time and space as political categories, first, we explore the temporal-spatial frames of political analysis.Second, we study the history of political time and space as ideas and facts.Third, we analyze the metaphorical use of the concepts in a political context, and we draw analogy to the physical notions of time and space. Finally,we present the various manifestations and understandings of the political time and space nowadays.